Weakly compatible maps in 2-non-Archimedean Menger PM-spaces - Renu Chugh; Sanjay Kumar (International Journal of Mathematics and Mathematical Sciences)
The aim of this paper is to introduce the concept of weakly compatible maps in 2-non-Archimedean Menger probabilistic metric (PM) spaces and to prove a theorem for these mappings without appeal to continuity. We also provide an application.